New Zealand & Polynesian records from colonial missionaries, 1838-1958. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
This collection comprises the C series records relating to the early history of the Anglican Church in Aotearoa New Zealand and Polynesia (C/NZ), along with selected volumes from the series of copies of letters sent and received (CLR & CLS), consists of files relating to the establishment of the Society's activities in the province, and the development of a diocesan organisation to support them. Correspondence was entered into by the SPG, the Colonial Office in London and the ecclesiastical officers in the colonies. The records also include printed reports, annual returns, and financial statements almost a hundred years, from the second quarter of nineteenth century, with the addition of one volume of letters received from the Diocese of Honolulu, in the north of the Polynesian region, over a forty year period from the 1870s until it fomally became part of the Episcopal Church in America. Of special interest among the papers relating to the diocese of Melanesia is the private correspondence and journal of its first bishop, John Coleridge Patteson.
Date range: 1838-1958.
Keywords: Church of the Province of New Zealand -- Liturgy and ritual; Anglican Communion -- New Zealand -- Liturgy and ritual